1994
DOI: 10.1111/j.1699-0463.1994.tb04879.x
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of immunoreactivity by hydrated autoclaving, microwave treatment, and simple heating of paraffin‐embedded tissue sections

Abstract: The effects of treatment in a hydrated autoclave (121 °C, 2 atm for 20 min), microwave oven (in water), and simple heating (60 °C overnight in distilled water or 90 °C for 10 min in ZnSO4) on the stainability of 56 antigens by commercially available antibodies in formalin‐fixed paraffin‐embedded tissue sections were evaluated. The detectability of nuclear antigens, glycoprotein, lymphocytic surface markers, and chromogranin A was significantly and reproducibly improved by these treatments, whereas the detectab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 9 publications
0
33
0
Order By: Relevance
“…The fact that high-temperature heating is the most important factor for retrieval of antigens masked by formalin fixation was demonstrated by Shi et al (1991) and in many subsequent applications of AR-IHC in pathology Igarashi et al 1994;Kawai et al 1994a;Lucassen et al 1993;Suurmeijer and Boon 1993a;Malmstrom et al 1992). Higher temperature in general yields better results of AR-IHC.…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations
“…The fact that high-temperature heating is the most important factor for retrieval of antigens masked by formalin fixation was demonstrated by Shi et al (1991) and in many subsequent applications of AR-IHC in pathology Igarashi et al 1994;Kawai et al 1994a;Lucassen et al 1993;Suurmeijer and Boon 1993a;Malmstrom et al 1992). Higher temperature in general yields better results of AR-IHC.…”
Section: Methodsmentioning
confidence: 98%
“…For example, Kawai et al (1994b) found that heating at 90C for 10 min was more effective than heating at 60C for 120 min. Different heating methods have been used for AR-IHC, such as autoclaving (Pons et al 1995;Bankfalvi et al 1994;Igarashi et al 1994;Umemura et al 1994;Shin et al 1991), pressure cooking (Miller and Estran 1995;Norton et al 1994), water bath (Kawai et al 1994b), microwaving (MW) plus plastic pressure cooking Pertschuk et al 1994), and steam heating (Pasha et al 1995;Taylor et al 1995). Again, the temperature achieved by these methods appears to be the critical variable.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, gastrointestinal tumor specimens are notoriously difficult to handle using standard FISH and conventional cytogenetic techniques because of frequent necrosis, contamination with inflammatory and normal stromal cells, and the poor attachment of the tumor cells (Kitayama et al, 1995). Present techniques involving the use of microwave ovens for antigen retrieval (Igarashi et al, 1994;Taylor et al, 1994) in formalin-fixed, paraffinembedded tissues have led to the suggestion that FISH signals might be enhanced if an appropriate heat treatment is included during sample preparation. To avoid the above-mentioned problems associated with paraffin sections, the FISH protocol was thus modified to incorporate an intermittent, short-term microwave (MW) treatment during the initial period of hybridization.…”
mentioning
confidence: 99%